Schwierigkeiten im Gebrauch der deutschen Unterrichtssprache - ILUK, Jan (Wydawcnictwo Naukowe UAM, 1994)
A very important problem for the foreign language teacher and learner is: how to use the foreign language structures correctly not only as paradigms but also as please, thank, question, aunswer or in other speech acts. The author thinks that the teacher should have at hislher disposal a full repertoire of such classroom phrases and be able to use them in all situations. Further he gives the semantic and structural description of some most often used German sentences contrasted with their Polish and English equivalents to eliminate the interlingual interference.